1999
DOI: 10.1038/sj.bjc.6990559
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones inhibit intestinal epithelial cell proliferation and induce apoptosis in vitro

Abstract: The incidence of intestinal cancer is high in Western populations but is relatively uncommon in Asia and Africa (Boyle et al, 1985). It is thought that this variation in incidence is strongly influenced by diet (Armstrong and Doll, 1975;Adlercreutz, 1990) and it is estimated that about 32% of deaths by all cancers, and 70% of deaths from colorectal cancer, could be prevented by a change in diet (Willet, 1995). There is also evidence to suggest that a high intake of soya-based foods (as in populations of Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The inhibition of intestinal cellular proliferation by genistein in vivo supports that observed in vitro by our group (22) and others (19,20,44). In vitro studies have delineated a possible mechanism underlying the biphasic effects of genistein for cell proliferation.…”
supporting
confidence: 72%
“…The inhibition of intestinal cellular proliferation by genistein in vivo supports that observed in vitro by our group (22) and others (19,20,44). In vitro studies have delineated a possible mechanism underlying the biphasic effects of genistein for cell proliferation.…”
supporting
confidence: 72%
“…Our findings support a variety of studies that have linked the soy-derived isoflavones, such as genistein, with antitumorigenic activity [6,12]. Genistein has been demonstrated to reduce proliferation and induce G2/M phase arrest and apoptotic death in colon cancer HT-29 cells [40].…”
Section: Discussionsupporting
confidence: 77%
“…Among flavonoids, phytoestrogen genistein has drawn attention in recent years due to a variety of biological activities that may account for its cancer-preventive effects. In vitro experiments demonstrated that genistein influences proliferation, differentiation and apoptosis in different tumor cell types (85). The anticancer effects of genistein involve inhibition of angiogenesis, topoisomerase, tyrosine kinase activity and antioxidant processes (86).…”
Section: Thermophilus B Breve B Longum B Infantis L Acidophilmentioning
confidence: 99%